Greater exercise tolerance in COPD during acute interval, compared to equivalent constant‐load, cycle exercise: physiological mechanisms. (16th June 2020) - Louvaris, Zafeiris; Chynkiamis, Nikolaos; Spetsioti, Stavroula; Asimakos, Andreas; Zakynthinos, Spyros; Wagner, Peter D.; Vogiatzis, Ioannis
Abstract : Key points: Exercise intolerance is common in chronic obstructive pulmonary disease (COPD) patients. In patients with COPD, we compared an interval exercise (IE) protocol (alternating 30 s at 100% peak work rate (WRpeak ) with 30 s at 50% WRpeak ) with moderate‐intensity constant‐load exercise (CLE) at 75% WRpeak, which yielded the same work rate. Exercise endurance time and total work output were almost twice as high for IE than CLE. At exercise isotime (when work completed was the same between IE and CLE), IE was associated with less dynamic hyperinflation, lower blood lactate concentration, and greater respiratory and locomotor muscle oxygenation, but there were no differences in ventilation or cardiac output. However, at the limit of tolerance for each modality, dynamic hyperinflation was not different between IE and CLE, while blood lactate remained lower and muscle oxygenation higher with IE. Taken together, these findings suggest that dynamic hyperinflation and not muscle‐based factors dictate the limits of tolerance in these COPD patients. Abstract: The relative importance of ventilatory, circulatory and peripheral muscle factors in determining tolerance to exercise in patients with chronic obstructive pulmonary disease (COPD) is not known. In 12 COPD patients (forced expiratory volume in one second: 58 ± 17%pred.) we measured ventilation, cardiac output, dynamic hyperinflation, local muscle oxygenation, blood lactate and time to exhaustion during (a) interval exercise (IE) consisting of 30 s at 100% peak work rate alternating with 30 s at 50%, and (b) constant‐load exercise (CLE) at 75% peak work rate, designed to produce the same average work rate. Exercise time was substantially longer during IE than CLE (19.5 ± 4.8 versus 11.4 ± 2.1 min, p  = 0.0001). Total work output was therefore greater during IE than CLE (81.3 ± 27.7 versus 48.9 ± 23.8 kJ, p  = 0.0001). Dynamic hyperinflation (assessed by changes from baseline in inspiratory capacity, ΔIC) was less during IE than CLE at CLE exhaustion time (isotime, p  = 0.009), but was similar at exhaustion (ΔICCLE : ‐0.38 ± 0.10 versus ΔICIE : ‐0.33 ± 0.12 l, p  = 0.102). In contrast, at isotime, minute ventilation, cardiac output and systemic oxygen delivery did not differ between protocols ( P  > 0.05). At exhaustion in both protocols, the vastus lateralis and intercostal muscle oxygen saturation were higher in IE than CLE ( p  = 0.014 and p  = 0.0002, respectively) and blood lactate concentrations were lower (4.9 ± 2.4 mmol l ‐1 versus 6.4 ± 2.2 mmol l ‐1, p  = 0.039). These results suggest that (1) exercise tolerance with COPD is limited by dynamic hyperinflation; and (2) cyclically lower (50%) effort intervals in IE help to preserve muscle oxygenation and reduce metabolic acidosis compared with CLE at the same average work rate; but these factors do not appear to determine time to exhaustion. Key points: Exercise intolerance is common in chronic obstructive pulmonary disease (COPD) patients. In patients with COPD, we compared an interval exercise (IE) protocol (alternating 30 s at 100% peak work rate (WRpeak ) with 30 s at 50% WRpeak ) with moderate‐intensity constant‐load exercise (CLE) at 75% WRpeak, which yielded the same work rate. Exercise endurance time and total work output were almost twice as high for IE than CLE. At exercise isotime (when work completed was the same between IE and CLE), IE was associated with less dynamic hyperinflation, lower blood lactate concentration, and greater respiratory and locomotor muscle oxygenation, but there were no differences in ventilation or cardiac output. However, at the limit of tolerance for each modality, dynamic hyperinflation was not different between IE and CLE, while blood lactate remained lower and muscle oxygenation higher with IE. Taken together, these findings suggest that dynamic hyperinflation and not muscle‐based factors dictate the limits of tolerance in these COPD patients.